Improvement in the absorbency of ozone bleached cotton fabric by the addition of surfactant. Issue 11 (15th October 2021) - Arooj, Fariha; Jamshed, Kainat; Kashif, Saif ur Rehman; Jamshed, Haroon; Luqman, Muhammad
Abstract: The combined effect of surfactants with ozone bleaching process on the quality of cotton fabric was examined in this paper. The concentration of surfactants was varied between 0.01- 0.5 g/l in order to evaluate its effect on CIE whiteness, absorbency and strength of cotton fabric bleached by ozone. The maximum improvement in absorbency (1.07 s) and whiteness (WCIE 66.53) was achieved in the presence of anionic surfactant (0.01 g/l) at optimized experimental conditions. The strength properties of cotton fabric bleached by ozone in the presence of surfactant were also improved. Pollution load of ozone bleaching effluent even after adding surfactant was far less than conventional bleaching effluent. Statistically it was confirmed that surfactant addition significantly improved the whiteness and absorbency of ozone bleached cotton fabric.